Elektronske cigarete sa različitim koncentracijama nikotina u tečnosti bez ukusa izazivaju oksidativni stres - Ismail, Naufal Arif; Mahmuda, Ardian Rizki Maarif; Firdaus, Rifqi; Ahsani, Dwi Nur (Scripta Medica, 2023)
Background/Aim: Nicotine content and flavour in electronic cigarette (e-cig) liquids have been demonstrated to cause oxidative stress in acute exposure. However, the chronic effects of using unflavoured and with or without nicotine in e-cigs liquid have not been evaluated. This in vivo study aims to investigate the chronic effect of e-cig exposure with unflavoured liquids at different nicotine concentrations on oxidative stress. Methods: The 24 male Wistar rats were divided into four groups of six each. Normal, as a control group. Nic 0, Nic 6 and Nic 12 groups were exposed to unflavoured e-cig liquid for eight weeks with different nicotine concentrations: 0, 6 and 12 mg/mL, respectively. E-cig exposure in rats was conducted using an exposure instrument adjusted to real-life exposure to humans. Oxidative stress markers, including plasma, liver and lung malondialdehyde (MDA) and superoxide dismutase (SOD), as well as plasma catalase (Cat) and glutathione peroxidase (GPx) were assessed at the end of the study. Results: Unflavoured e-cig liquids induced oxidative stress in a nicotine concentration-dependent manner, in which the nicotine content of 12 mg/mL demonstrated the greatest response. There was a significant increase in plasma, liver and lung MDA and concurrently decreased plasma and selected organs SOD, as well as plasma Cat and GPx in all nicotine concentration exposed groups compared to the Normal group. Conclusions: Chronic unflavoured liquids in e-cig exposure at different nicotine concentrations induced oxidative stress, potentially leading to various oxidative stress-induced diseases.